A Comparative Study of Internet Use in Haryana Agriculture University and Panjab Agriculture University - Sharma, Chetan (Journal of Information and Knowledge, 2008)
The study examines the status and use of the Internet in Punjab Agricultural University and Haryana Agricultural University. A well structured questionnaire was distributed among the 200 teachers and research scholars of both the agriculture universities under study. Findings of this study show that Internet is being heavily used for e-mail and research purpose and also highlight purposes and frequency of use of the Internet by the teachers and research scholars, their method of locating, accessing and using information on the net. The study also discusses the problems that are preventing wide use of the Internet in both the universities.